Spin transfer torque induced domain wall oscillations in ferromagnetic nanowire with a nanoscale Dzyaloshinskii–Moriya interaction region - Kumar, Durgesh (2020)
The interfacial Dzyaloshinskii–Moriya Interaction (iDMI) in ferromagnetic (FM)/heavy metal (HM) structures has been under intense investigation due to the interesting observation of many novel chiral structures such as domain walls (DWs) and skyrmions. In all the studies so far, the iDMI is present in the whole of the FM layer. In this study, we report our investigations on a FM nanowire where iDMI is confined to a nanoscale region. We observe that the local modulation of magnetic properties results in oscillations of DWs under the influence of spin-transfer torque (STT). For such oscillations, the nanoscale iDMI acts as a restoring force. We have studied the dependence of oscillation frequency upon the current density, geometrical parameter (width of nanoscale iDMI region), strength of iDMI and magnetic parameters such as anisotropy constant (Ku), exchange constant (A) and saturation magnetization (Ms). The variation in the above-mentioned parameters results in the tunability of oscillation frequency within a few GHz. Moreover, the amplitude of oscillations is also tunable with the width of the nanoscale iDMI region. These observations make this study potentially useful for applications in neuromorphic computing.